2010
DOI: 10.1007/s11557-010-0691-4
|View full text |Cite
|
Sign up to set email alerts
|

RAPD and ISSR markers indicate high genetic variation within Lobathallia radiosa in Turkey

Abstract: Randomly amplified polymorphic DNA (RAPD) and inter simple sequence repeat (ISSR) methods were used for investigating genetic variation within L. radiosa and for delimiting species within the genus Lobothallia. Ten RAPD and 11 ISSR primers produced a total of 261 and 260 reproducible bands, respectively, and all of which were polymorphic for the two markers, suggesting high genetic variability within L. radiosa. Genetic distances between the samples of L. radiosa for the RAPD and ISSR analyses ranged from 51 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
4
7
0
Order By: Relevance
“…Such a high genetic diversity between local populations of lichens has been already described [2,13]. Moreover, another studies have shown even higher intraspecific genetic diversity than noted in our research, e.g., in the lichen species Lobothallia alphoplacaand, L. radiosa [14] or in the fungus Pisolithus tinctorius [15]. The reason of such high genetic may be the habitat whose isolation reduces the flow of genes between populations [16][17][18].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Such a high genetic diversity between local populations of lichens has been already described [2,13]. Moreover, another studies have shown even higher intraspecific genetic diversity than noted in our research, e.g., in the lichen species Lobothallia alphoplacaand, L. radiosa [14] or in the fungus Pisolithus tinctorius [15]. The reason of such high genetic may be the habitat whose isolation reduces the flow of genes between populations [16][17][18].…”
Section: Discussionsupporting
confidence: 79%
“…The reason of such high genetic may be the habitat whose isolation reduces the flow of genes between populations [16][17][18]. The high variation is an important trait because it plays a role under environmental changes, determining the survival of organisms [14,19,20]. The evaluation of two analyzed groups of H. physodes, the first growing on the bark of pine trees and the second on the sand, confirms the hypothesis that lichens are sensitive to substrate features [21].…”
Section: Discussionsupporting
confidence: 53%
“…As a result of the amplifications with the use of the examined Viburnum genotypes, 1160 (RAPD) and 873 (ISSR) amplicons were scored as the effect of amplification of 690 RAPD and 418 ISSR loci, respectively. The length of the amplified products corresponded to the number of products amplified, the number of primers used, and the length of products mostly generated with these methods and presented in papers by Sharma et al (2009), Williams et al (1990), Yüzbaşioğlu et al (2011) and Zietkiewicz et al (1994). We demonstrated high genetic variability among the examined Viburnum objects.…”
Section: Issr Analysis Assessment Of Genetic Diversity Between Thirteenmentioning
confidence: 88%
“…Genotype-specific ISSR products generated for 13 genotypes of Viburnum reasons, such as delimitation of species, conservation of endangered species, analysis of the population' structure of a species and construction of phylogenetic relationships among species in fungi, plants and animals (Yüzbaşioğlu et al, 2011). The invention of PCR led to the development of fast and inexpensive molecular markers, such as RAPD and ISSR (Arseniuk 2000; Czembor and Sharma et al, 2009;Gajera et al, 2011;Godwin et al, 1997;Williams et al, 1990;Yüzbaşioğlu et al, 2011). Because of the longer primers used, ISSR markers reported to be more reproducible than RAPD markers (Godwin et al, 1997).…”
Section: Issr Analysis Assessment Of Genetic Diversity Between Thirteenmentioning
confidence: 99%
See 1 more Smart Citation